Percepção ambiental dos gestores de meios de hospedagem: estudo de caso em Caxias do Sul-RS - Ferrari, Patricia Flores (My University, 2014)
The objective of this study is to verify the environmental perception of the managers of lodging establishments in Caxias do Sul (RS), regarding environmental quality and its importance in the operationalization of their own activities. A structured interview based on a script of 44 questions applied to 21 people (lodging establishment managers) was the technique used for data collection. Results show that 76.19% of interviewees revealed to be uninformed about management of environmental practices in lodging establishments and also general matters related to environmental issues. It is also possible to identify a direct relationship between general knowledge and education of the interviewees. Results have lead to the identification of gaps in teaching programs and in environmental management in the areas of Tourism and Hotel Management, regarding environmental responsibility, acknowledgement and complying with environmental laws. It was also possible to identify the relationship between environmental perception and conduct intentions from managers of lodging establishments. In synthesis, in order to these managers have an effective environmental perception, we propose an update on Tourism and Hotel Management courses with the insertion of environmental aspects, as well as interventions concerning sensibilization activities to guests and staff, information regarding environmental legislation, responsibility to hotel activities relating to its environmental impact and tourism planning, taking into consideration the environment variable.
Este estudo tem por objetivo verificar qual a percepção ambiental dos gestores de meios de hospedagem no município de Caxias do Sul (RS), com relação à qualidade ambiental e sua importância na operacionalização das próprias atividades. A técnica empregada para a coleta de dados foi a entrevista estruturada, embasada num roteiro de 44 questões. Foram feitas entrevistas com 21 sujeitos (gestores de meios de hospedagem). Os resultados demonstram que 76,19% das indicações dos sujeitos revelam estar desinformados sobre o gerenciamento de práticas ambientais em meios de hospedagem e assuntos gerais relacionados às questões ambientais; possibilitam ainda evidenciar a relação direta entre nível geral de informação dos sujeitos entrevistados e o grau de escolaridade. Os resultados permitiram identificar lacunas nos programas de ensino e na gestão ambiental, na área de turismo e hotelaria, quando o assunto é responsabilidade com o meio ambiente, conhecimento e cumprimento da legislação ambiental; bem como a relação existente entre a percepção ambiental e as intenções de conduta dos gestores de meios de hospedagem. Em síntese, para que a percepção ambiental desses gestores seja efetiva, propõe-se a modernização dos cursos de turismo e hotelaria com a inserção da dimensão ambiental, bem como, a intervenção junto a eles, no que diz respeito a atividades de sensibilização para hóspedes e funcionários, informações sobre a legislação ambiental, responsabilidade das atividades hoteleiras em relação ao impacto ambiental das mesmas e, ao planejamento do turismo contemplando a variável ambiental.
Keywords: Turismo; Planejamento e gestão; Percepção ambiental; Meios de hospedagem; Caxias do Sul (RS); Tourism; Planning and management; Environmental perception; Lodging establishments; Caxias do Sul (Brazil); Gestão ambiental